The Preferences of Consumers When Selecting Clothing Detergent Products - Kamwendo, Andrew R.; Maharaj, Mandusha (International Review of Management and Marketing, 2022)
The retailing environment has shown that consumer purchases are dependent upon the consideration and subsequent evaluation of product attributes. Consumer’s selection of products are driven by their preferences for the attributes that the products possess. The aim of this study was to investigate product attribute preferences for cross-category shopping products in Durban. The quantitative study design based on a cross-sectional descriptive survey was conducted. The study population consisted of consumers within the city of Durban. The study sampled 213 students selected from three universities in Durban (University A, B and C). Research respondents were chosen using convenience sampling. Respondents were purposely selected based on their capacity to give meaningful information relevant to the study. The Cronbach alpha test was conducted to test for reliability of the first instrument. The results indicated acceptable, consistent scoring patterns for the sections of the research instrument. The study revealed that for clothing detergent products, product form is the most important attribute followed by product effectiveness. It is important to note that significant differences were found in the respondent's preferences for product attributes in terms of the respondent's demographics. For clothing detergents, significant differences were found in terms of respondents preferences for the price, scent, size and product form of clothing detergents. Subsequently, generalised product attribute preferences were obtained. The findings of the study are limited due to the low response rate among older respondents. Future studies may benefit from investigating sub-categories. Moreover, future studies should consider other consumer segmentation methods in order to better understand and classify retail behaviour when developing modelling approaches. Retail managers may benefit from communicating more value for money for their skincare product offerings. Brands that are synonymous with longer lasting products either through offering more volume or products that require less application to achieve desired results may provide a competitive advantage.